Analisis Metode SCRUM dalam Pengembangan E-IAPT 4.0 STMIK Royal Berbasis CodeIgniter - Rolly Yesputra; Nasrun Marpaung (Universitas Putra Indonesia YPTK Padang, 2023)
Accreditation is essential for a tertiary institution as a form of recognition of the quality of existing education. Accreditation is very closely related to the management of tertiary institutions, so each tertiary institution must keep all evidence of the activities that have been carried out. To facilitate the management of evidence of tri-dharma activities that have been carried out, It must create a system that can be used to meet these needs. STMIK Royal still needs an application that can be used to manage data for accreditation needs. In this research, the E-IAPT 4.0 information system will be developed using the SCRUM method, which is the reference in developing this software. With the SCRUM method, the software development process is expected to run faster and easier. The SCRUM method has a considerable influence on the software development process. Scrum values ​​for a project team include commitment, courage, focus, openness, and respect. In the process of this research using qualitative methods. Analysis was conducted by studying existing software and conducting discussions or interviews with STMIK Royal management to determine system requirements. The developed system can already be applied to STMIK Royal